The Path to Paradise: A Comparative Study of Tafsir Al-Munir and Tafsir Al-Qurthubi - Irania Cahyanti; Bukhori Abdul Shomad; Kiki Muhamad Hakiki (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This article aims to examine the interpretations of Imam al-Qurṭubī and Imam Wahbah al-Zuḥaylī concerning the verses on al-laghw as a path toward attaining Paradise (al-Firdaus) in QS. al-Mu’minūn verse 3, as well as to identify the similarities and differences between al-Qurṭubī’s interpretation and that of Tafsīr al-Munīr regarding al-laghw in the same verse. This study is a library-based research employing a comparative (muqārran) method. The research process begins with a general explanation of the concept of al-laghw in relation to attaining Paradise (al-Firdaus), followed by an analysis of the perspectives of the two exegetes. The findings indicate that the term al-laghw appears in eleven verses of the Qur’an and generally refers to futile speech and actions, or words and deeds that bring no benefit. Among its meanings are all forms of immorality and polytheism (shirk). The significance of this research lies in providing insight into how verses concerning al-laghw are interpreted from the perspectives of al-Qurṭubī and Tafsīr al-Munīr, the analytical approaches employed by both exegetes, and the Qur’anic solutions for avoiding al-laghw. It is expected that this study will serve as a scholarly reference that enriches collective understanding in fostering good moral character and avoiding reprehensible traits, one of which is al-laghw.